2016
DOI: 10.1007/s40256-016-0203-2
|View full text |Cite
|
Sign up to set email alerts
|

Sebelipase Alfa: A Review in Lysosomal Acid Lipase Deficiency

Abstract: Sebelipase alfa (Kanuma, Kanuma™), the first commercially available recombinant human lysosomal acid lipase (LAL), is approved in various countries worldwide, including those of the EU, the USA and Japan, as a long-term enzyme replacement therapy for patients diagnosed with LAL deficiency (LAL-D), an ultra-rare, autosomal recessive, progressive metabolic liver disease. In an ongoing study in nine infants presenting with early-onset LAL-D (Wolman disease), open-label treatment with sebelipase alfa significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
16

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 18 publications
0
30
0
16
Order By: Relevance
“…Mutations in the LIPA gene cause lysosomal storage diseases such as Wolman disease and cholesteryl ester storage disease 30 . For treatment of LIPA deficiency, Kanuma (Sebelipase alfa), which is a recombinant LIPA produced by transgenic chicken egg, was approved for use in 2015 in the USA and EU 31 . We constructed vectors carrying His6-Flag-tagged LIPA (sHF-LIPA) or sHF-LIPA fused with a GPI-attachment signal (sHF-LIPA-GPI), which were stably expressed in cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the LIPA gene cause lysosomal storage diseases such as Wolman disease and cholesteryl ester storage disease 30 . For treatment of LIPA deficiency, Kanuma (Sebelipase alfa), which is a recombinant LIPA produced by transgenic chicken egg, was approved for use in 2015 in the USA and EU 31 . We constructed vectors carrying His6-Flag-tagged LIPA (sHF-LIPA) or sHF-LIPA fused with a GPI-attachment signal (sHF-LIPA-GPI), which were stably expressed in cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the pharmacoeconomics associated with the cost-effectiveness of a treatment such as ERT would thus be of interest. 10 A recent study in the United Kingdom evaluated the costs of managing children and adults with LAL deficiency in a tertiary centre, and found these to be staggering. In light of this, consideration needs to be given to rare diseases in policy and budgetary decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for LALD was historically supportive until 2015 with Food and Drug Administration (FDA) approval of enzyme replacement therapy (ERT). The recombinant enzyme, sebelipase alfa, is given once every 2 weeks as an intravenous infusion and is taken up by target tissues, predominantly the liver, via the mannose-6-phosphate receptor [6]. A Phase III trial of biweekly enzyme replacement for 52 weeks demonstrated dramatic clinical and biochemical improvement, including normalization or near-normalization of alanine aminotransferase (ALT) levels, improved lipid parameters including reduction in low-density lipoprotein cholesterol (LDL-C) and triglycerides and increased high-density lipoprotein cholesterol (HDL-C) levels, and decreased hepatic fat content [7].…”
Section: Introductionmentioning
confidence: 99%